Cerebrotendinous xanthomatosis with a novel mutation in CYP27A1 gene in a Turkish patient - Dikbas, Oguz; Torun, Deniz; Ilgezdi, Irem; Eyuboglu, Ilker; Unlu, Burcu (Annals of Medical Research, 2021)
None